Die Konzepte der flexiblen Produktion und der Industriedistrikte als Erklärungsansätze der Regionalentwicklung - Sternberg, Rolf (ERDKUNDE, 1995)
The concept of flexible production and industrial districts and their applicability as theories of regional development According to the theories of flexible production/specialisation and strongly connected industrial districts, a new wave of economic growth is being led in a number of regions in advanced economies by spatially concentrated networks of mostly small and medium sized enterprises, normally using flexible production technology and characterized by extensive local inter-firm linkages. On the basis of the relevant literature, this paper tries to assess the value of both concepts regarding their applicability as theories of regional development. Three criteria are used to evaluate the concepts. First, causality is investigated concerning their basic hypotheses. Second, we ask, whether the basic hypotheses are transferable to all industries and types of regions. In order to test for empirical validity, a third group of aspects will be discussed around the question of quality and quantity of empirical studies upon industrial districts. Fourth, the potential for policy conclusions is in the centre of interest. Both concepts are valuable because they combine mainly well-known hypotheses from economic theory (e. g., localisation and urbanisation effects) and social sciences (culture, embeddedness, and common historical background as reasons for firm growth and intra-regional linkages) in a new kind of concept of regional development. In addition to that, they take into account the steadily growing importance of networks and flexibility in production processes. However, three main deficiencies considerably decrease their value as regional development concepts. First, essential hypotheses like the local dominance of innovative networks and the comparative advantages of SME within these networks have to be characterized as yet unproved. Second, flexible economies in the sense of industrial districts are the exception to the rule of economies dominated by large companies integrated into international and global networks. Finally, in the respective literature promising regional development policies, based upon industrial district theory, are difficult to find.